Hierarchical control and emulation of a wave energy hyperbaric converter - Isaac R. Machado; Paula B. Garcia‐Rosa; Edson H. Watanabe (IET Renewable Power Generation, 2021)
Abstract Wave energy emulators provide an option to extend studies of wave energy converters (WECs) in an electric power laboratory facility and to evaluate the performance of controllers in an experimental set‐up. In addition, the integration of control strategies in different steps of the energy conversion process is an important step to improve the WEC overall behaviour that has not yet been widely discussed. This paper proposes a real‐time emulator and a hierarchical control scheme for a hyperbaric WEC consisting of floating bodies, hydropneumatic storage system (HSS), hydraulic turbine, and doubly fed induction generator (DFIG). The proposed emulator is based on a typical electric power laboratory facility, where a numerical model reproduces the dynamics of the wet subsystem and a hardware is the WEC electrical subsystem. Thereby, a squirrel‐cage induction motor (SCIM) is coupled shaft‐to‐shaft with the DFIG. The SCIM reproduces the characteristics of torque and speed that would be observed in the real system, and then, the DFIG is subjected to a primary drive with same dynamic characteristics of the real plant. The hierarchical control integrates the generator and HSS controllers considering the optimal operating pressure for local sea state conditions. Experimental results illustrate the performance of the emulator and controllers.